2020
DOI: 10.3390/ijerph17176383
|View full text |Cite
|
Sign up to set email alerts
|

Does Believing in Fate Facilitate Active or Avoidant Coping? The Effects of Fate Control on Coping Strategies and Mental Well-Being

Abstract: The development of control-related constructs has involved different approaches over time, and yet internal and external locus of control are conceptualized as dichotomous factors influencing active versus avoidant coping strategies. While external control is associated with avoidance, a similar belief construct fate control, which denotes that life events are pre-determined and influenced by external forces but predictable and alterable, challenges the assumption of incompatibility between fate and agency. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 91 publications
1
5
0
Order By: Relevance
“…The results revealed that subjective well-being was associated with different neurocognitive domains (e.g., executive control, episodic memory, complex cognition, and social cognition) in a sample of Spanish adolescents. A third article aimed to understand the relationship between control and response to stress in the prediction of mental well-being in university and undergraduate students in Hong Kong [ 35 ]. The results showed that while external control was positively related to avoidant coping, fate control was positively related to both active and avoidant coping.…”
Section: Resultsmentioning
confidence: 99%
“…The results revealed that subjective well-being was associated with different neurocognitive domains (e.g., executive control, episodic memory, complex cognition, and social cognition) in a sample of Spanish adolescents. A third article aimed to understand the relationship between control and response to stress in the prediction of mental well-being in university and undergraduate students in Hong Kong [ 35 ]. The results showed that while external control was positively related to avoidant coping, fate control was positively related to both active and avoidant coping.…”
Section: Resultsmentioning
confidence: 99%
“…These findings in the Zimbabwean context also confirmed Chitereka and Nduna's (2010) conclusions regarding rural contraceptive consumer behaviour. More recently, Wu et al (2020) noted the relationship between fate control and coping styles.…”
Section: Results and Discussion Of Findingsmentioning
confidence: 99%
“…Second, when individuals who suffer unavoidable constraints of their fate (flood and COVID-19), deny that there exist constraints of their fate, or do not believe that their efforts could compensate their fate, they may choose more passive coping strategies and negative cognition reappraisal [ 21 , 22 , 60 ]. They may tend to ignore the potential social resources of their parents; thus, their high PCRs would not help them to actively cope with the strain in disasters.…”
Section: Discussionmentioning
confidence: 99%